MODERN STYLES OF DIPLOMATIC SUPPORT FOR FOREIGN ECONOMIC ACTIVITY - PUKHALSKA, Yana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the contemporary styles of supporting foreign economic activity by the diplomatic service of Ukraine in the context of rapid global transformations. Emphasis is placed on the evolution of approaches to organizing economic diplomacy under the influence of globalization, digitalization, and growing geopolitical turbulence, particularly in conditions of war, sanctions, and shifting international alliances. The authors characterize the main styles of diplomatic support for foreign economic activity, distinguishing technocratic, network-based, strategic, innovative, and public-communication approaches. Each style is examined in terms of its strengths, limitations, and challenges that modern diplomatic institutions face, with special attention to the need for their integrated, adaptive application to enhance efficiency and resilience.The study highlights the growing role of digital technologies, information platforms, and instruments of public diplomacy in shaping a positive image of Ukraine in international markets, strengthening trust, and expanding long-term partnerships with foreign economic actors. A particular focus is given to how innovative and communicative tools can reinforce Ukraine’s competitiveness, open new opportunities for cooperation, and counter disinformation threats.Furthermore, the article outlines the prospects for developing styles of economic diplomacy in the context of Ukraine’s European integration. It emphasizes the importance of aligning national practices with European standards and policies that incorporate principles of sustainable development, digital transformation, inclusiveness, and public–private partnership. The authors also underline the challenges of training a new generation of diplomats capable of working effectively in a multidimensional, technology-rich environment, combining analytical expertise, intercultural competence, and strategic vision.The article makes a timely contribution to advancing both the theoretical framework and the practical tools of ensuring foreign economic activity under the complex realities of the modern geoeconomic environment.
Keywords: foreign economic activity; diplomatic service; economic diplomacy; diplomacy styles; digitalization; public diplomacy; international cooperation